Online Gambling Practices (Positive Legal, Social, And Religious Review) - Hudjolly Hudjolly*; Firmansyah Firmansyah; Rohyani Rigen Sumilat; Nety Novita Hariyani; Kalijunjung Hasibuan (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to determine (1) the practice of online gambling in Indonesia in terms of positive law; (2) how online gambling practices are viewed from a social perspective; and (3) online gambling practices in terms of religion. This research is normative juridical research. Researchers examine the norms in positive law. The primary data source used in this research is the ITE Law (Act on Information and Electronic Transactions) related to online gambling law enforcement, while the secondary data source used in this research is previous research that is relevant to the discussion of online gambling practices in Indonesia. The results of this study indicate that (1) Article 27 paragraph 2, Article 45 paragraph 1, and Article 52 paragraph 4 of the ITE Law regulate prohibitions and criminal sanctions related to online gambling in Indonesia. The government needs to improve preventive and repressive measures in regulating online gambling crimes to minimize crime in Indonesia; (2) The practice of online gambling brings complex problems, online gambling players will justify any means to get money so that their desire to play gambling can be fulfilled, this is feared to lead to other criminal acts and unsettle the community; (3) the majority of religions in Indonesia prohibit gambling because it can have negative effects that are detrimental to society.